Children's reading difficulties, language, and reflections on the simple view of reading. Issue 1 (2nd January 2019) - Nation, Kate
ABSTRACT: Reading comprehension is a complex task which depends on a range of cognitive and linguistic processes. According to the Simple View of Reading, this complexity can be captured as the product of two sets of skills: decoding and linguistic comprehension. The Simple View explains variance in reading comprehension and provides a good framework to guide the classification of reading disorders. This paper discusses how weaknesses in either or both of components of the Simple View are implicated in children's reading comprehension difficulties. It concludes with reflections on the strengths and limitations of the Simple View as a theoretical and practical framework to guide our understanding of reading comprehension and its development.